Geologia, petrografia e geocronologia das rochas encaixantes do granito paleoproterozóico São João, sudeste de Craton Amazônico, Província de Carajás - MESQUITA, Jardel Carlos Lima (2019)
The host rocks of the Paleoproterozoic São João granite, located in the Água azul do Norte region, Rio Maria Granite-Greenstone Terrane (RMTGG), southeastern Amazonian Craton, are dominantly represented by Archean thondhjemites and potassic leucogranites. The geologic mapping allowed to characterize the spatial distribution of these rocks, their structural aspects, and estimates its dimensions. Trondhjemites and potassic leucogranites outcrop in the form of small hills, big blocks, and flooring with a slight NW-SE structure. They are cut by several metric mafic and felsic dykes also structured in a NW-SE. The potassic leucogranites are textural and compositionally homogeneous, almost always monzogranítica in composition. They occur in the form of an ellipsoidal body, which is cut in the SSW edge by the São João Granite and extends to the eastern boundary of the Seringa Granite. The trondhjemite rocks dominate in the south portion of the São João Granite and its southern and eastern limits beyond the area delimited for this study. Macroscopically these rocks are medium to-coarse grained and light gray in color. In general, show compositional banding with light bands, rich in felsic minerals, and dark bands, rich in mafic minerals, with NW-SE foliation. Semi-quantitative chemical analysis using SEM-EDS on zircons and biotites performed in the potassic leucogranites and trondhjemite rocks of this study showed great similarities with zircons and biotites of the Xinguara leucogranite and Mogno Trondhjemite located to northeast of Xinguara and north of Bannach cities, respectively. Geochronological dating by Pb evaporation in zircon crystals also showed great similarities to the ages of these latter two units, but the high contents of Pb204 identified in the dated zircons did not allow conclusive ages to the rocks of the Água azul do Norte region.